1992
DOI: 10.1007/bf00238255
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of nutrients and phytoplankton, and fluxes of carbon, nitrogen and silicon in the Antarctic Ocean

Abstract: Summary. Four major functional units have been identified in the Southern Ocean and the mechanisms that control the dynamics of nutrients and phytoplankton are detailed for the different sub-systems. The very productive Coastal and Continental Shelf Zone (CCSZ, 0.9 M kmZ) can experience severe macronutrient depletion paralleling intense diatom-dominated phytoplankton blooming (maximum> 8 mg ChI a m -3) at the ice edge. In the Seasonal Ice Zone (SI Z, 16 M km 2 ), dramatic variations in the hydrological struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
91
0
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 239 publications
(97 citation statements)
references
References 0 publications
4
91
0
2
Order By: Relevance
“…These rate are 50% or more higher than other modelbased or measured rates of production in the APF, and up to two or more times greater than other estimates in the SIZ (Wefer and Fischer, 1991;Tr! eguer and Jacques, 1992;Qu!…”
mentioning
confidence: 58%
“…These rate are 50% or more higher than other modelbased or measured rates of production in the APF, and up to two or more times greater than other estimates in the SIZ (Wefer and Fischer, 1991;Tr! eguer and Jacques, 1992;Qu!…”
mentioning
confidence: 58%
“…High phytoplankton concentrations ð41:0 mg m À3 Þ are found below 60 m in the study area (El-Sayed and Weber, 1982;Bianchi et al, 1992;Tre´guer and Jacques, 1992;Smith et al, 1996;Whitehouse et al, 1996). Deep chlorophyll maxima have been observed mostly in the summer/fall in the Scotia Sea (El-Sayed and Weber, 1982), western Antarctic Peninsula (Bianchi et al, 1992;Tre´guer and Jacques, 1992;Smith et al, 1996) and near South Georgia (Whitehouse et al, 1996); they are not observed during winter/spring (El-Sayed and Weber, 1982;Smith et al, 1996).…”
Section: Deep Chlorophyll Maximummentioning
confidence: 86%
“…Deep chlorophyll maxima have been observed mostly in the summer/fall in the Scotia Sea (El-Sayed and Weber, 1982), western Antarctic Peninsula (Bianchi et al, 1992;Tre´guer and Jacques, 1992;Smith et al, 1996) and near South Georgia (Whitehouse et al, 1996); they are not observed during winter/spring (El-Sayed and Weber, 1982;Smith et al, 1996). Due to limited data this feature was not included in this modeling approach, although it may well be one additional food source available to krill in summer.…”
Section: Deep Chlorophyll Maximummentioning
confidence: 99%
“…The continental slope is defined by steep, rapidly deepening bathymetry between the shelf and the deep sea (750-3000 m water depth). With regard to Antarctic marine ecosystem types defined by Treguer and Jacques (1992), BS can be attributed to the 'Coastal and Continental Shelf Zone' and the DP to the 'Continental Shelf Edge and Slope', consistent with respective bathymetry, ocean dynamics and water masses (Ducklow et al 2007). …”
Section: Methodsmentioning
confidence: 93%